Hubungan antara Corporate Governance dan Variabel Pengurang Masalah Agensi - Zaenal Arifin (Jurnal Siasat Bisnis, 2005)
The main objective of this research is to investigate whether there are a significant relationship be¬tween corporate governance and agency-problem-reducing variables. The corporate governance is concern on all stakeholders’ interest while the agency variables are concern on one of the most important stakeholders’ that is the stockholders-interest. Theoretically, there should be a significant relationship between the corporate govern¬ance and the agency-problem-reducing variables. Using 52 Indonesian listed companies in 2001 that had been investigated by Indonesian Institute for Corporate Governance (IICG) for the companies’ practice of corporate governance and presented on SWA Magazine, this research found that no relationship between the corporate governance and the agency-problem-reducing variables. There are some possible explanations for this finding. First, reducing agency problems does not perceived (by investor) affecting the companies’ practice of corporate governance. Second, the bonding mechanisms to reduce the free cash flows by increasing the dividend payment or increasing the debt and monitoring by the independent board of directors are not an effective mechanism to re¬duce agency problems. So these mechanisms do not correlate to the companies’ practice of corporate govern¬ance. Third, the score of corporate governance released by IICG are not valid. Further investigations are needed to find the true explanation.Key words: Corporate Governance, Masalah Agensi